Consensus for the Development of a New Early Warning Score for Predicting Patients’ Clinical Deterioration in Angola: A Delphi Study - Esmael Tomás; Ana Escoval; Maria Lina Antunes (Critical Care Research and Practice, 2024)
Conclusion: Angolan experts were able to identify the physiological parameters suitable for incorporation into the basic EWSs. Further study must be conducted to test and validate the impact of the newly suggested vital parameters on the discriminant and predictive capability of a new aggregated model specifically adjusted to the Angolan healthcare setting.